Impact of Butter, Margarine, and Coconut Oil on the Sensory Quality of Baked Brownies: A Descriptive Sensory Analysis Approach - Lucy Fridayati; Reska Mayefis; Ifnalia Rahayu; Nadira Ulfach (Journal of Food and Pharmaceutical Sciences, 2026)
This study investigated the effect of different fat sources; butter, margarine, and coconut oil on the sensory quality of baked brownies using a descriptive sensory analysis approach. Sensory evaluation was conducted based on five organoleptic attributes: shape, color, aroma, texture, and taste. The experiment employed a completely randomized design (CRD) consisting of three treatments with three replications. Sensory data were collected from five expert panelists using a structured hedonic questionnaire and subsequently analyzed using analysis of variance (ANOVA), followed by Duncan’s multiple range test when significant differences were detected. The results indicated that the substitution of butter with margarine or coconut oil did not produce statistically significant differences (p > 0.05) across all sensory attributes evaluated. Although brownies formulated with butter generally obtained slightly higher mean scores, particularly for aroma, texture, and flavor intensity, these differences were not sufficient to demonstrate a significant treatment effect. All formulations exhibited comparable sensory profiles characterized by a dense and moist crumb, a dry surface texture, a blackish-brown color, and a characteristic chocolate flavor. These findings suggest that margarine and coconut oil can serve as viable alternatives to butter in brownie production without compromising overall sensory quality. The study provides practical implications for bakery product formulation by supporting flexibility in fat selection based on economic, nutritional, or availability considerations rather than sensory performance alone.